Partial oxidation of methane over Fe/ZSM-5 with hydrogen peroxide generated in situ over Pd/C in the presence of halide ions - Kang, Jongkyu; Park, Eun Duck (Catalysis Today, 2024)
The effect of halide ion on the catalytic activity for the aqueous-phase partial oxidation of methane with H2O2 generated in situ over Pd/C was examined. Various halide ions, including F-, Cl-, Br-, and I- were compared. Among them, Br- and I- are effective for the synthesis of H2O2 from H2 and O2, resulting in the synthesis of methane oxygenates from methane over Fe/ZSM-5. They show different product yields as a function of their concentrations. The highest total product yields were obtained with [KBr] = 5 mM and [KI] = 0.05 mM, respectively. Compared with Br-, the highest product yield was obtained with a much lower concentration of I-, guaranteeing that no detectable leaching of metal from Fe/ZSM-5 and Pd/C was found. The total productivity was 4.64 mmol/gcat./h over Fe/ZSM-5 at 50 ℃ with H2O2 generated in situ over Pd/C from H2 and O2 in the presence of 0.05 mM of KI.
Keywords: 2-generated; Aqueous phasis; Fe/ZSM-5; Halide ions; Low concentrations; Methane oxygenate; Partial oxidations of methane; Pd/C; Product yields; Fe/ZSM-5; Formic acid; Halide ion; Hydrogen peroxide; Methane oxygenates; Partial oxidation of methane; Pd/C